PENINGKATAN ABSORBANSI MAKSIMUM ASAM b-(2-FURIL) AKRILAT MELALUI MODIFIKASI STRUKTUR - Mitarlis, (Matematika dan Sains, 2009)
Improving maximum absorbance (lmax) of b-(2-furyl) acrylic acid by modification structure had been done. The research was done on three stages, the first was activity test to b-(2-furyl) acrylic acid as the raw material of the sunscreen compound in vitro at several values of pH using UV-Vis spectrophotometer. The second was structure modification of â-(2-furyl) acrylic acid became octyl b-(2-furyl) acrylic and the last was activity test of octyl of â-(2-furyl) acrylic. Base on this research, b-(2-furyl) acrylic acid had wavelength of maximum absorption before pH conditioning was the same as that of pH 7, namely 295 nm. While it shifted to shorter value (290 nm) at pH 4,5,6 and to longer value (300 nm) at pH 8, 9. After modification became octyl-b-(2-furyl) acrylic, it had wavelength of maximum absorption between 303,00 - 304,20 nm and relative stable in several pH.lmax) of b-(2-furyl) acrylic acid by modification structure had been done. The research was done on three stages, the first was activity test to b-(2-furyl) acrylic acid as the raw material of the sunscreen compound in vitro at several values of pH using UV-Vis spectrophotometer. The second was structure modification of â-(2-furyl) acrylic acid became octyl b-(2-furyl) acrylic and the last was activity test of octyl of â-(2-furyl) acrylic. Base on this research, b-(2-furyl) acrylic acid had wavelength of maximum absorption before pH conditioning was the same as that of pH 7, namely 295 nm. While it shifted to shorter value (290 nm) at pH 4,5,6 and to longer value (300 nm) at pH 8, 9. After modification became octyl-b-(2-furyl) acrylic, it had wavelength of maximum absorption between 303,00 - 304,20 nm and relative stable in several pH.